Rural and urban poverty models on Sumatra Island - Candra Mustika; Rahma Nurjanah (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
This study aims to analyze rural and urban poverty on Sumatra Island, Indonesia, and its determinants. The variables tested in the model are HDI (Human Development Index), GRDP (Gross Regional Domestic Product), and per capita expenditure. The data used is panel data for the provinces on Sumatra Island in the period 2011 - 2019. The analysis tool uses a panel data regression model. The study results found that during the 2011 - 2019 period, the rural poverty rate on Sumatra Island was 11.68 percent, relatively higher than in urban areas, 9.22 percent. The poverty gap index and poverty severity index in rural areas are also relatively higher than in urban areas. The research results also found that the poverty level in rural areas is significantly affected by HDI, while the GRDP and per capita expenditure does not significantly affect.